Primary Oral Malignant Melanoma: Two Case Reports and Review of Literature - Neeraj Sharma (Case Reports in Dentistry)
Primary malignant melanoma of the oral cavity is a rare neoplasm. The tumors tend to metastasize or locally invade tissue more readily than other malignant tumors in the oral region. The survival of patients with mucosal melanomas is less than for those with cutaneous melanomas. Tumor size and metastases are related to the prognosis of the disease. Early detection, therefore, is important.